The effect of facebook advertising towards customers from managerial perception a case study at Felcra Berhad / Syasya Aliah Yusof - Yusof, Syasya Aliah (2017)
Social media is the main marketing tools that used by the business ventures to promoting the products to ensure that the consumer aware with the organizations products. Previously, (AyarekarM.S, 2015) mentioned that, any well-known companies are experiencing operational change in their conventional practices in order to adapt to this online environment for advertise their products and services global (AyarekarM.S, 2015). Which are most of the organizations changed the technique of promoting that standardized with the modern technology. For the organizations it is important to have an expertise to promoting the products in the social media.